Ptyctimous mites (Acari, Oribatida) in the fauna of North Africa, against the background of the Palaearctic fauna - Niedbała, Wojciech (Biological Letters, 2013)
The ptyctimous mite fauna of each zoogeographical region of the world is highly specific and includes many endemic or native species. In Palaearctic Region it comprises 295 known species. The number of widespread species is very low: 14 semicosmopolitan, 16 Holarctic, and 15 pan-Palaearctic. Out of the relatively narrowly distributed species, over half (114) have also been noted as endemic to the Palaearctic Region. Twenty-seven species are known to originate from other zoogeographical regions and have been introduced to the Palaearctic in prooriental and East-Asiatic parts. The fauna of North Africa has a much lower number of endemic species than the neighbouring subregions, but a high number of Palaearctic species and a relatively high number of widespread species. This fauna is completely different from the Afrotropical fauna on the same continent. The majority of common species are West Palaearctic. The fauna of North Africa is much poorer in species than that of North Mediterranean subregion, but both these faunas share a lot of common species, especially many of West Palaearctic origin. Moreover, in North Africa the regional faunas show poor similarity, e.g. the fauna of the western islands (Canary Island and Madeira) is very different from that of Maghreb (Algeria, Morocco, Tunisia).